Visual Programming for Virtual Reality Applications Based on InTml - Figueroa, Pablo A (Journal on Interactive Systems, 2012)
This paper presents our work on a visual programming environment (VPE) for portable, implementation-independent, virtual reality (VR) applications. Previously, we have defined InTml, the Interaction Techniques Markup Language , a domain specific language for VR applications, and some initial, command-line based development tools. By using the concept of Model Driven Development (MDD) and with the aid of tools from the Eclipse Graphical Modeling Project (GMF), we built an IDE for VR applications, that allows the visual description of components, application creation, and code generation to targeted runtime environments in C++, Java, and ActionScript. We report some advantages and shortcomings in this approach for tool development, some results from our preliminary user studies and lessons learned. In general, an MDD based approach to VPE is challenging both in terms of learning curve and usability of the final IDE.